Insights on caesarean section in the southern tamandua (Tamandua tetradactyla) - Gomes, Diego Rodrigues [UNESP]; de Camargo, Gabriel Corrêa [UNESP]; Lacerda, Zara Alves [UNESP]; Oba, Eunice [UNESP]; de Souza, Fabiana Ferreira [UNESP] (Wiley, 2025)
Abstract An adult female southern tamandua ( Tamandua tetradactyla ) was rescued and taken to a veterinary centre for wildlife care. The patient's evaluation revealed an abnormal neurological status, along with prostration, diarrhoea, dehydration and bilateral corneal ulcers. Insecticide poisoning (carbamate, organophosphate or organochlorine) and canine distemper were initially considered as possible diagnoses, and supportive treatment was instituted. During screening with abdominal ultrasound and radiographic examinations, an advanced pregnancy stage was identified. Four days after its admission, the female experienced profuse oral and vaginal bleeding, abdominal contractions and fetal heart rate oscillations. The team decided to wait for natural delivery or abortion, considering the female's vulnerable clinical condition. Fetal death was confirmed by ultrasound within the following 12 hours, leading to an emergency caesarean section. The surgical approach was successful, and the patient showed progressive clinical improvement, returning to the natural environment after a month of recovery.